ANALYSIS OF KIDS CORNER SERVICES AS AN INNOVATION IN CHILDREN'S LITERACY AT THE UPT LIBRARY OF UIN FATMAWATI SUKARNO BENGKULU - Vivo Tri Ayunda Pantino; Lailatus Sa’diyah; Aang Gunaidi (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
Research on children's literacy services through kids corners generally focuses on spatial design and service activities, while functional analysis of children's library services in the context of university libraries is still relatively limited. This study aims to analyze the implementation of kids' corner services as a children's literacy innovation at the UPT Library of UIN Fatmawati Sukarno Bengkulu through an adaptation of the children's library service framework according to Akanwa (2013). The study used a qualitative approach with data collection techniques through observation, semi-structured interviews, and documentation of the managing librarian and teacher accompanying literacy activities. The results show that the kids' corner service not only functions as a provider of children's reading collections, but also as a space for early literacy learning that integrates the provision of information, development of reading skills, formation of cultural knowledge, and participatory learning about library utilization. However, optimization of collection diversity and program consistency are still needed to strengthen the sustainability of the service. This study offers conceptual novelty through the adaptation of the children's library service framework to the context of university libraries and systematically mapping the implementation of children's literacy services as a service evaluation model. Practically, the research findings provide a basis for developing a kids' corner service model that is more structured, sustainable, and has the potential to be replicated in other university libraries.